A tailored e-learning gives long-term changes in determinants of GPs' benzodiazepines prescribing: a pretest-posttest study with self-report assessments. (2nd October 2019) - Creupelandt, Hanne; Anthierens, Sibyl; Habraken, Hilde; Sirdifield, Coral; Siriwardena, Aloysius Niroshan; Christiaens, Thierry
Abstract: Objective: Despite guidelines and campaigns, general practitioners (GPs) continue to overprescribe benzodiazepines (BZDs). New approaches to improve prescribing are needed. Using behavior change techniques and tailoring interventions to user characteristics are vital to promote behavior change. This study evaluated the impact of a tailored e-learning module on factors known to determine BZD prescribing within GPs. Design: A pretest-posttest study design with three self-report assessments concerning determinants of BZD prescribing: at baseline, immediately after the module (short term) and six months after completion (long term). Setting: Flanders (Belgium) Intervention: A tailored e-module that focuses on avoiding initial BZD prescriptions and using psychological interventions as an alternative. Subjects: 244 GPs Main outcome measures: Assessed determinants include GPs' attitudes concerning treatment options, perceptions of the patient and self-efficacy beliefs. Readiness to adhere to prescribing guidelines was evaluated through assessing motivation, self-efficacy and implementability of non-pharmacological interventions. Results: A significant and durable impact on determinants of BZD prescribing was observed. GPs underwent desirable changes in attitudes, perceptions and self-efficacy beliefs and these changes remained significant six months later. Conclusion: Tailoring an e-intervention to target group characteristics appears to be successful in promoting behavioral change in experienced GPs. Significant and lasting changes were observed in determinants of prescribing BZDs. Key Points: A tailored e-intervention resulted in significant and long term changes in previously identified determinants of prescribing BZDs. The e-module resulted in a positive impact on GPs' readiness to adhere to BZD prescribing guidance and the way they experience psychosocial consultations. Tailoring an e-intervention to target group characteristics appears to be successful in promoting behavioral change in experienced GPs.